Increase of liver stiffness and altered bile acid metabolism after triple CFTR modulator initiation in children and young adults with cystic fibrosis - Schnell, Alexander; Jüngert, Jörg M.; Klett, Daniel; Hober, Hannah; Kaiser, Natalie; Ruppel, Renate; Geppert, Annika; Tremel, Christina; Sobel, Julia; Plattner, Erika; Schmitt-Grohe, Sabina; Zirlik, Sabine; et al. (Liver International, 2023)
Background: Novel cystic fibrosis transmembrane conductance regulator (CFTR) modulator therapies (elexacaftor/tezacaftor/ivacaftor—ETI) promise clinically significant and sustained improvements for patients with cystic fibrosis (CF). In this study, we investigated the impact of ETI therapy on liver stiffness and bile acid metabolism in a cohort of children and young adults with CF. Methods: A prospective observational study (NCT05576324) was conducted from September 2020 to November 2021 enrolling CF patients naive to ETI. Standard laboratory chemistry, sweat test, lung function, share wave velocity (SWV) derived by acoustic radiation force impulse imaging (ARFI) and serum bile acid profiles were assessed before and 6 months after induction of ETI therapy. Results: A total of 20 patients (10 aged <20 years) completed the study. While lung function and BMI improved after ETI therapy, ARFI SWV increased in CF patients <20 years of age (from 1.27 to 1.43 m/s, p = 0.023). Bile acid (BA) profiles revealed a decrease in unconjugated (5.75 vs 1.46, p = 0.007) and increase in glycine-conjugated derivatives (GCDCA) (4.79 vs 6.64 p = 0.016). There was a positive correlation between ARFI SWV values and GCDCA (r = 0.80, p < 0.0001). Glycine-conjugated BA provided high diagnostic accuracy to predict increased ARFI measurements (AUC 0.90) and clinical (Colombo) CFLD grading (AUC 0.97). Conclusions: ARFI SWV and bile acid profiles provide evidence for early increase in liver stiffness and altered bile acid metabolism in young CF patients after initiation of ETI and may serve as synergistic measures for detection of hepatic complications during ETI therapy.
CRIS-Team Scopus Importer:2023-03-17
Keywords: ARFI; bile acids; CFLD; cystic fibrosis